Alteration of N6-Methyladenosine mRNA Methylation in a Human Stem Cell-Derived Cardiomyocyte Model of Tyrosine Kinase Inhibitor-Induced Cardiotoxicity - Ma, Yan; Liu, Xian; Bi, Yiming; Wang, Tianhu; Chen, Cheng; Wang, Yabin; Han, Dong; Cao, Feng (Frontiers in Cardiovascular Medicine, 2022)
Background: N6-methyladenosine (m6A) has been revealed to play important roles in various cardiovascular diseases (CVD), including cardiac hypertrophy, heart failure, etc. Tyrosine kinase inhibitor (TKI) is widely used in the treatment of different types of solid and blood tumors, whereas its efficacy is restricted by a concomitant rise in cardiotoxicities. However, the methylation modification of m6A mRNA in cardiomyocytes treated with TKI has not been investigated. Results: In the present study, we observed that m6A methylation level was significant elevated in SUN-treated human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs), paralleled with a positively correlated cellular damage level. Through a genome-wide analysis of m6A mRNA methylation by MeRIP-Seq (methylated RNA immunoprecipitation sequencing) and RNA-seq (RNA sequencing, input), we identified a total of 2614 peaks with significant changes, of which 1695 were significantly up-regulated and 919 were significantly down-regulated. qRT-PCR, immunofluorescence and Western bolt revealed that RNA demethylase FTO was down-regulated, whereas RNA methylase METTL14 and WTAP was up-regulated. Furthermore, gain and loss of function studies substantiated that FTO is cardio-protective in TKI. Conclusion: This study deciphered the methylation modification of m6A mRNA in hiPSC-CMs post TKI treatment and determined that FTO may be a promising therapeutic target for TKI-induced cardiotoxicity.